Dental material composition package

A packaging bag with a cyclic polyolefin resin film addresses the weight loss issue of fluorine-containing (meth)acrylate in dental materials, ensuring stable storage and improved operability by reducing permeability.

JP2025006267APending Publication Date: 2025-01-17TOKUYAMA DENTAL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023106952
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

Smart Images

  • Figure 2025006267000005
    Figure 2025006267000005
  • Figure 2025006267000006
    Figure 2025006267000006
  • Figure 2025006267000007
    Figure 2025006267000007
Patent Text Reader

Abstract

To provide a paste-like dental material composition package in which a dental material composition containing a fluorine-containing (meth)acrylate monomer and a filler is liquid-tightly accommodated inside a bag body, in which the fluorine-containing (meth)acrylate does not volatilize and decrease even when the package is stored for a long period of time.SOLUTION: A bag body is made of a single-layer or multi-layer resin film having a layer containing a cyclic polyolefin resin made of a cyclic polyolefin polymer or a cyclic polyolefin copolymer, which is a polyolefin resin having a cyclic aliphatic hydrocarbon in a main chain or a side chain.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaged dental material composition, specifically a packaged dental material composition in the form of a slurry or paste. [Background technology]

[0002] In the dental field, materials used as prostheses and restorations include radical polymerizable monomers, inorganic particles, crosslinked / non-crosslinked resins, and hardened dental hardenable compositions containing radical polymerization initiators. Such dental hardenable compositions are usually made into a highly viscous paste in which solids such as fillers are uniformly dispersed in a liquid such as a monomer when used, and the dental hardenable composition is generally used as a prosthesis or restoration by performing a shaping or molding operation inside or outside the oral cavity and then polymerizing and hardening the composition by the action of a radical polymerization initiator. Representative examples of paste-like dental hardenable compositions include dental composite resins (CR), dental cements, denture base lining materials, and denture base repair materials. For example, dental composite resins (CR) are repair materials for repairing teeth damaged by caries, fractures, and the like. In addition, dental cements are adhesives used to fix metal or ceramic crown repair materials to teeth. Furthermore, denture base relining materials or denture base repair materials are repair materials that are used to reline the denture base surface that has become out of fit to the oral mucosa when the denture that is being worn becomes out of fit due to bone resorption, deformation of the mucosal surface, etc., in order to refit the denture.

[0003] As radical polymerization initiators used in dental paste-like hardenable compositions, chemical polymerization initiators (room temperature redox initiators consisting of a combination of an oxidizing agent and a reducing agent), photopolymerization initiators, thermal polymerization initiators, etc. are used. When using a chemical polymerization initiator, in order to prevent polymerization hardening during storage, each component is generally divided into two or more dental material compositions (materials or agents) so that the oxidizing agent, reducing agent, and monomer do not coexist, and these dental material compositions are mixed at the time of use to prepare a dental paste-like material (preparation just before use in this way is called "preparation at the time of use"). At this time, the two or more dental material compositions can take the form of "powder", "liquid", "slurry", or "paste" depending on their composition.

[0004] For "preparation just before use", it is necessary to take (weigh) and mix each required amount of each dental material composition, but there is also known a package form (suitable for preparation just before use) that eliminates the need for weighing and makes mixing easier. For example, for CR and dental cement, which are used in small amounts, a so-called "double syringe type" container with two barrels integrated is used, and a package is known in which two paste-like dental material compositions (to be packaged separately) are stored and held in each barrel. Then, when using, after setting in a dispenser as necessary, a nozzle tip type mixer mounting mechanism called a mixing tip is attached to the discharge port of each syringe, and the two plungers are pushed into each barrel in conjunction with each other using fingers directly or via the dispenser, and the paste-like CR or dental cement prepared just before use by mixing and preparing in the mixing tip is extruded from the tip of the mixing tip to the desired position for application.

[0005] Also, for denture base relining materials and denture base repair materials, which are not only used in large quantities but also require a relatively long time from preparation to hardening from the viewpoint of operability, and for which the pace and properties during that time are important, a different packaging form from the above-mentioned has been proposed. That is, Patent Document 1 describes a packaging form for so-called "powder-liquid type" dental materials for denture base relining materials and denture base repair materials, which are prepared just before use using two types of material compositions, a powder material and a liquid material, in which "the bag body is partitioned into a plurality of sealed storage chambers, weakened parts that separate each storage chamber are formed between each storage chamber, the weakened parts are formed so as to be rupturable by a pressing force applied to the bag body, and after the weakened parts are ruptured, the storage chambers are connected to each other, and the contents stored in these storage chambers are packed into a single container. "A dental powder and liquid material preparation storage bag" is disclosed, which is characterized in that the dental powder and liquid material is composed of a powder material containing an organic polymer and a liquid material that dissolves the powder material and changes to a paste-like state in cooperation with the powder material, and the bag body is formed so that the powder material that changes to a paste-like state and the liquid material can be pressed via the surface of the bag body after the weakened part is broken. And, by using the above-mentioned "dental powder and liquid material preparation storage bag", it is not necessary for the user, the dentist, to measure two materials (powder material and liquid material) when using the product, and the work is simplified.

[0006] Incidentally, as the radical polymerizable monomer (monomer) used in the paste-like dental material, a (meth)acrylate-based polymerizable monomer is generally used, but in recent years, the advantage of using a fluorine-containing (meth)acrylate as the (meth)acrylate-based polymerizable monomer has been attracting attention. For example, it has been reported that, regarding dental composite resins and dental resin cements using a photopolymerization initiator, the use of a fluorine-containing (meth)acrylate as a monomer provides excellent transparency, curing depth, surface hardness and mechanical strength of the cured product (see Patent Document 2). It has also been reported that the use of a fluorine-containing (meth)acrylate in a denture base lining material provides a denture base lining material that is less prone to coloring of the cured product and absorbs and adsorbs odorous components (see Patent Document 3). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-223237 A [Patent Document 2] Patent Publication No. 2021-80196 [Patent Document 3] JP 2000-312689 A Summary of the Invention [Problem to be solved by the invention]

[0008] From the viewpoint of the above-mentioned effects of using fluorine-containing (meth)acrylate, it is considered effective to use fluorine-containing (meth)acrylate as a monomer for use in the liquid material even in the packaging form of the "powder-liquid type" dental material disclosed in Patent Document 1. However, Patent Document 1 does not disclose any examples of using such a liquid material.

[0009] Therefore, the present inventors prepared a package containing a liquid material (dental material composition) containing fluorine-containing (meth)acrylate in a pouch body using a film made of polyethylene or polypropylene as disclosed in Patent Document 1, and conducted an investigation, which revealed that a problem occurred in storage stability. That is, an investigation was conducted. Specifically, the presence or absence of change (storage stability) of the above package when stored for a long period of time was evaluated by a thermal accelerated deterioration test using a thermostatic bath at 60°C, and it was revealed that the weight of the fluorine-containing (meth)acrylate of the paste-like dental material contained therein was reduced. If the weight of the fluorine-containing (meth)acrylate is reduced, the ratio (filling rate) of the fluorine-containing (meth)acrylate and the filler, which were previously stored in an appropriate amount in the package, will change, and the desired operability (paste properties) will not be obtained after long-term storage.

[0010] Therefore, the present invention aims to provide a technology that prevents weight loss of a fluorinated (meth)acrylate during storage, even when a dental material composition containing a fluorinated (meth)acrylate is contained in a package made of a resin film. [Means for solving the problem]

[0011] The present invention is to solve the above-mentioned problems, and one form of the present invention is a dental material composition package comprising a bag having a storage chamber, and a slurry or paste-like dental material composition containing a polymerizable monomer and a filler, the dental material composition being liquid-tightly stored in the storage chamber, the polymerizable monomer containing a fluorine-containing (meth)acrylate, and the bag being constituted by a single-layer film or a multilayer film having a layer containing a cyclic polyolefin resin.

[0012] In the dental material composition package of the above form (hereinafter also referred to as "the package of the present invention"), it is preferable that the layer containing the cyclic polyolefin resin is made of a resin composition containing 5 to 70 mass% of a cyclic polyolefin resin and the remainder being a polyolefin resin having no ring structure.

[0013] In addition, the single-layer film or multi-layer film having a layer containing a cyclic polyolefin resin is preferably a heat-sealable film.

[0014] In addition, in an embodiment having a bag body made of the above-mentioned heat-sealable film, the bag body has at least one weakened seal portion and at least two of the storage chambers separated by the at least one seal portion, The slurry or paste dental material composition containing a fluorine-containing (meth)acrylate as a polymerizable monomer is contained in at least one of the at least two containing chambers, At least one of the at least two storage chambers may contain a slurry or paste dental material composition containing a polymerizable monomer not containing a fluorinated (meth)acrylate and a filler, a liquid dental material composition containing a polymerizable monomer and not containing a filler, or a powder dental material composition containing a filler and not containing a polymerizable monomer, At least one of the dental material compositions contained in each of the containers contains a polymerization initiator, the weakened seal portion is formed so as to be breakable by a pressing force applied to at least one of the at least two storage chambers in which the dental material composition is stored; It is preferable that after the weakened seal portion is broken, the respective storage chambers are connected to each other so that all the types of dental material compositions contained in these storage chambers can be mixed in the connected storage chambers to prepare a paste-like dental hardenable composition containing a polymerizable monomer containing a fluorinated (meth)acrylate, a filler and a polymerization initiator.

[0015] Furthermore, in the package of the present invention in the above-mentioned preferred embodiment (hereinafter also referred to as "package for preparing a paste-like dental curable composition of the present invention"), the polymerization initiator includes a chemical polymerization initiator composed of two or more components each of which does not exhibit polymerization activity alone, Each of the dental material compositions contained in each storage chamber contains at least one of the two or more components constituting the chemical polymerization initiator, but does not contain all of the two or more components, Each of the two or more components constituting the chemical polymerization initiator is preferably contained in any one of the dental material compositions contained in each of the containers.

[0016] It is also preferable that air is contained in at least one of the storage chambers so that the volume of air in the connected storage chambers at room temperature when mixing the paste-like dental material is in the range of 15 to 40% of the volume of the storage chamber. Effect of the Invention

[0017] According to the package of the present invention, not only a slurry or paste-like dental material composition (which can be said to be a raw material composition of these materials) used for preparing denture base relining materials and denture base repair materials when used, but also a dental hardenable composition such as photopolymerizable or thermosetting CR can be stored in a resin bag in a required amount of fluorine-containing (meth)acrylate as a monomer component, and can be stably stored for a long period of time. In particular, when the package of the present invention for preparing a dental hardenable paste composition is used, it is possible to not only save the trouble of weighing each dental material composition when preparing a dental hardenable paste when used, but also to simplify and streamline the kneading operation, although it does not use a so-called "powder material", as with the dental powder material-containing dispensing bag disclosed in Patent Document 1. Furthermore, in cases where the powder material and liquid material do not mix well at the start of kneading, the initial kneading properties can be improved by adding a small amount of monomer to the powder material in advance to make a viscous paste-like material, and storing the (remaining) liquid material in the package for preparing the paste-like dental curable composition of the present invention. [Brief description of the drawings]

[0018] [Figure 1] 1A and 1B are plan views of packages according to an embodiment of the present invention, in which (A) is a package having one storage chamber, and (B) is a package having two storage chambers. [Diagram 2] FIG. 2 is a plan view of a packaging body for preparing a paste-like dental hardenable composition according to an embodiment of the present invention. [Diagram 3] FIG. 2 shows the procedure for preparing a paste-like dental hardenable composition and its use, in which (A) shows the state in which one of the storage chambers is pressed to break the weakened seal, (B) shows the state in which the surface of the bag body is pressed with a mixing tool while being kneaded, and (C) shows the state in which the paste-like dental material, which has been made uniform by mixing, is removed from the bag. [Figure 4]FIG. 1 shows cross-sectional views of three types of multilayer films suitable for use in a prescription storage bag according to an embodiment of the present invention; (A) is a film consisting of two layers, a base layer and a sealant layer; (B) is a film consisting of three layers, a base layer, an intermediate layer and a sealant layer; and (C) is a film consisting of five layers, consisting of a base layer, an adhesive layer, an intermediate layer, an adhesive layer and a sealant layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The package of the present invention is a bag having a storage chamber, the inside of which is filled with a dental material composition containing a fluorine-containing (meth)acrylate in a liquid-tight manner, and is characterized in that the bag is made of a single-layer film or a multilayer film having a layer containing a cyclic polyolefin resin. Here, the dental material composition means a composition used as a dental material or a raw material thereof, specifically a composition containing a polymerizable monomer and a filler, and is a concept including the dental curable composition and a composition that is an "agent" or "material" (a raw material for the dental curable composition) used when preparing the dental curable composition when used.

[0020] As mentioned above, when a dental material composition containing a fluorine-containing (meth)acrylate is stored for a long period of time in a storage chamber of a bag body made of a film made of polyethylene or polypropylene, a weight loss occurs, and the cause of this is thought to be that the fluorine-containing (meth)acrylate permeates the resin film constituting the bag body due to its high volatility. That is, since polyethylene and polypropylene have relatively wide gaps between polymer chains and low resin density, it is thought that the vapor of the fluorine-containing (meth)acrylate permeates the film made of these resins.

[0021] As a method for suppressing the permeation of gas into a film, a method of providing a metal-containing barrier layer such as aluminum for the purpose of increasing the airtightness of the package is generally known. However, when such a method is adopted, it becomes impossible to visually check the amount of the contents. In particular, in the case of a package such as that disclosed in Patent Document 1, when two or more pastes are prepared in the package at the time of use, the degree of mixing of the pastes cannot be visually confirmed, so the method of providing a metal barrier layer is not suitable.

[0022] Therefore, the present inventors came up with the idea of ​​using a transparent resin as a barrier layer to suppress the weight loss of the liquid material during storage without reducing visibility, and conducted research. As a result, when nylon was used as a barrier layer, which is a transparent resin with a low oxygen permeability coefficient used as an index of gas permeability, a low resin free volume (intermolecular space), and a high specific gravity (density), a sufficient weight loss suppression effect was not obtained. On the other hand, the inventors found that the desired effect could be obtained when a cyclic polyolefin resin was used as a barrier layer, and thus completed the present invention.

[0023] The inventors of the present invention presume that the weight loss could not be sufficiently suppressed when nylon was used, whereas a high suppression effect was obtained when a cyclic polyolefin resin was used, as follows. That is, both nylon and cyclic polyolefin resins have strong intermolecular interactions between polymer chains, and are resins that are expected to exert an effect of suppressing the permeability of gas molecules. On the other hand, since fluorine-containing (meth)acrylate has strong polarity derived from carbon-fluorine bonds, it is easily dissolved and diffused in nylon resin, which also has strong polarity, whereas cyclic polyolefin resins have low polarity, and therefore it is difficult for molecules with strong polarity such as fluorine-containing (meth)acrylate to dissolve and diffuse, resulting in low permeability. It is known that, when the permeability coefficient of a substance (A) in a specific resin material (B) is P, the solubility coefficient is S, and the diffusion coefficient is D, the relationship P=S×D holds; the larger the permeability coefficient P, the greater the amount of permeation. However, since the above S and D are determined for each combination of A and B, it is difficult to predict the barrier property against fluorinated (meth)acrylates, for example, from the tendency of the barrier property effect against oxygen and water vapor.

[0024] The paste-like dental material to be packaged in the package of the present invention, the resin film constituting the bag of the package of the present invention, and the package of the present invention will be described in detail below. In the present specification, unless otherwise specified, the expression "x to y" using the numerical values ​​x and y means "x or more and y or less". In such an expression, when a unit is added only to the numerical value y, the unit is also applied to the numerical value x. In this specification, the term "(meth)acrylate" means both "acrylate" and "methacrylate".

[0025] 1. Dental material composition to be packaged The dental material composition to be packaged in the package of the present invention is not particularly limited as long as it is a composition used as a dental material or a raw material thereof, contains a polymerizable monomer containing a fluorine-containing (meth)acrylate and a filler, and is a slurry or paste-like composition that does not polymerize and harden at least at room temperature under light protection (hereinafter, also referred to as "specific dental material composition"). Here, "does not polymerize and harden at least at room temperature under light protection" means that it does not contain a polymerization initiator consisting of a single component or multiple components that exhibits polymerization initiation ability at a temperature of 50°C or less, and it is acceptable to contain some components of a polymerization initiator consisting of multiple components in a state that does not exhibit polymerization initiation ability at a temperature of 50°C or less, or to contain a photopolymerization initiator and / or a thermal polymerization initiator (which does not exhibit polymerization initiation ability at a temperature of 50°C or less). For example, dental hardenable compositions used as dental composite resins (CR), dental cements, denture backing materials, pit and fissure sealants, loose tooth fixation materials, and orthodontic adhesives, or compositions used as raw materials for these dental hardenable compositions, which satisfy the above conditions, can be packaged in the package of the present invention.

[0026] Hereinafter, each component used in the specific dental material composition to be packaged in the package of the present invention will be described.

[0027] 1-1. Fluorine-containing (meth)acrylate monomer The specific dental material composition to be packaged in the package of the present invention contains a fluorine-containing (meth)acrylate as a polymerizable monomer. Here, the fluorine-containing (meth)acrylate means a (meth)acrylate compound having a fluorine atom in the molecule, and preferably, a fluorine-containing (meth)acrylate represented by the following general formula (I) is used.

[0028] CH2=C(R 1 )COO-R 2 -R f (I) In addition, in the above formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group, and R fIn the above formula (1), the group: -R is preferably used because the color of the cured product obtained when the compound is blended into a dental curable composition and cured is small, and the absorption and adsorption of odorous components is small, and the irritation to the oral mucosa is small. 2 -R f The number of carbon atoms in the above formula (1): -R is preferably 4 to 10, and the proportion of fluorine atoms in the total number of atoms (other than carbon atoms) bonded to carbon atoms in the above formula (1) is preferably 50% or more. 2 -R f When the carbon number is less than 4, the volatility of the fluorine-containing (meth)acrylate monomer is very high, and therefore, in terms of ease of handling when preparing the dental material composition and storage stability of the prepared dental material composition, it is preferable to use a fluorine-containing (meth)acrylate monomer having 4 or more carbon atoms.

[0029] Examples of suitable fluorine-containing (meth)acrylates include 1H,1H,3H-hexafluorobutyl methacrylate, 1H,1H,5H-octafluoropentyl methacrylate, 1H,1H,6H-decafluorohexyl methacrylate, 1H,1H,7H-dodecafluoroheptyl methacrylate, and 1H,1H,2H,2H-tridecafluorooctyl methacrylate. Among these five compounds, 1H,1H,6H-decafluorohexyl methacrylate and 1H,1H,7H-dodecafluoroheptyl methacrylate are particularly preferred. These fluorine-containing (meth)acrylate monomers may be used alone or in combination of two or more.

[0030] All of the polymerizable monomers contained in the specific dental material composition may be fluorine-containing (meth)acrylates. However, an increase in the proportion of fluorine-containing (meth)acrylates reduces the toughness of the cured product, while a decrease in the proportion of fluorine-containing (meth)acrylates reduces the discoloration resistance of the cured product and increases the adsorption of odorous components. For these reasons, the proportion of fluorine-containing (meth)acrylates in the total mass of polymerizable monomers is preferably 15 to 75 mass%, and particularly preferably 25 to 65 mass%.

[0031] In this case, as the polymerizable monomer other than the fluorine-containing (meth)acrylate, a (meth)acrylate copolymerizable with the fluorine-containing (meth)acrylate can be suitably used. Examples of such (meth)acrylates include monofunctional (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-(meth)acryloxyethyl propionate, and acetoacetoxyethyl (meth)acrylate; and polyfunctional (meth)acrylates such as 1,3-propanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate. When a polyfunctional (meth)acrylate is blended in a paste-like dental material, the toughness of the cured material is improved, and therefore it is preferable to use a polyfunctional (meth)acrylate.

[0032] 1-2. Filling material The filler contained in the specific dental material composition used in the package of the present invention may be any known filler that can generally be used in dental materials, such as a filler made of a non-crosslinked polymer, a filler made of a crosslinked polymer (excluding those that are completely soluble in the polymerizable monomer component), a filler made of an inorganic substance, or a filler made of a composite of an inorganic substance and a resin. One type may be used alone, or two or more types may be used in combination.

[0033] Examples of fillers made of non-crosslinked polymers that can be suitably used include homopolymers or copolymers of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate, and copolymers of (meth)acrylic acid monomers such as poly(styrene-ethyl methacrylate) and other polymerizable monomers, and one or more of them may be used in combination. In addition, when the specific dental material composition is a dental hardenable composition or a raw material composition thereof that is used as a denture base backing material or denture base repair material, it is preferable to use one having a solubility in fluorine-containing (meth)acrylate monomers of less than 20% by mass. Here, the solubility means the upper limit of the concentration at which a non-crosslinked polymer can be dissolved in a fluorine-containing (meth)acrylate monomer. Here, in the present specification, the solubility was simply determined by visually evaluating the concentration at which the non-crosslinked polymer is dissolved at 23°C when the non-crosslinked polymer is added to a polymerizable monomer in a range of 5% to 50% by mass of the fluorine-containing (meth)acrylate monomer.

[0034] As the filler made of crosslinked polymer, it is preferable to use one that is substantially insoluble in fluorine-containing (meth)acrylate monomer. Examples of the filler made of such crosslinked polymer include crosslinked polymers such as poly(meth)acrylate, polycarbonate, and polyester, among which, (meth)acrylic acid-based crosslinked polymer particles such as polymethyl methacrylate and polyethyl methacrylate are particularly suitable because they are inexpensive and easy to handle.

[0035] Examples of suitable fillers made of inorganic substances include silica, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, calcium carbonate, calcium sulfate, magnesium oxide, barium carbonate, barium sulfate, titanium oxide, potassium titanate, barium titanate, aluminum hydroxide, and magnesium hydroxide. One or more of these may be used in combination. In addition, it is preferable that the filler made of inorganic substances is surface-treated in advance with a surface treatment agent in order to improve the affinity with the fluorine-containing (meth)acrylate monomer or to increase the chemical bond with the fluorine-containing (meth)acrylate monomer to improve the mechanical strength of the cured product. Examples of the surface treatment agent include organic silicon compounds, organic titanium compounds, organic zirconium compounds, and organic aluminum compounds. These surface treatment agents may be used alone or in combination.

[0036] When the specific dental material composition is a dental hardenable composition or a raw material composition thereof that is to be used as a denture base lining material or a denture base repair material, it is preferable to use at least one selected from the group consisting of a filler made of a crosslinked polymer, a filler made of an inorganic substance, and a filler made of a composite of an inorganic substance and a resin, because of its low solubility in a fluorine-containing (meth)acrylate monomer. Also, when the specific dental material composition is a dental hardenable composition or a raw material composition thereof that is to be used as a CR or dental cement, it is preferable to use a filler made of an inorganic substance and / or a filler made of a composite of an inorganic substance and a resin.

[0037] There is no particular restriction on the shape of the filler, and it may be appropriately selected according to the properties to be enhanced as a dental composition. Specifically, powder of irregular (meaning the shape of crushed particles) or spherical particles may be used. It is known that the mechanical strength and abrasion resistance of the resulting hardened product are improved when a filler made of irregular particles (crushed particles) is used, and the polishing smoothness and smoothness durability of the resulting hardened product are improved when a filler made of spherical particles is used. In this specification, the filler being spherical means that the particles observed in a unit field of view of the filler taken with a scanning electron microscope (SEM) are rounded, and the average uniformity obtained by dividing the particle diameter in the direction perpendicular to the maximum diameter by the maximum diameter is 0.6 or more.

[0038] There is no particular restriction on the average particle size of these fillers, which is obtained from the volume percent D50 value measured using a laser diffraction / scattering particle size distribution device based on the Mie scattering theory, and may be selected appropriately according to the paste-like dental material to be prepared.

[0039] For example, when the specific dental material composition is a dental hardenable composition to be used as CR or dental cement, or a raw material composition thereof, from the viewpoints of the ease of handling of the dental hardenable composition and the mechanical strength of the obtained hardened product, the particle size is preferably 0.0001 to 50 μm, more preferably 0.001 to 10 μm, even more preferably 0.003 to 5 μm, and particularly preferably 0.005 to 1 μm.

[0040] Furthermore, when the specific dental material composition is a dental hardenable composition or a raw material composition thereof that is to be used as a denture base relining material or denture base repair material, the average particle size is preferably 0.01 to 100 μm, and more preferably 1 to 40 μm.

[0041] The content of the filler to be blended in the specific dental material composition is not particularly limited, and can be appropriately changed depending on the form of use, purpose, etc. For example, when the dental material composition is a dental curable composition to be used as a CR or dental cement, or a raw material composition thereof, the content is preferably 100 to 900 parts by mass, more preferably 140 to 600 parts by mass, and particularly preferably 200 to 450 parts by mass, relative to 100 parts by mass of the total polymerizable monomers contained in the dental material composition.

[0042] Furthermore, when the dental material composition is a dental hardenable composition or a raw material composition thereof that is to be used as a denture backing material or a denture repair material, it preferably contains 20 to 80 parts by mass per 100 parts by mass of the total polymerizable monomers contained in the dental material composition.

[0043] The total content of the fluorine-containing (meth)acrylate monomer and filler contained in the specific dental material composition can be appropriately changed depending on the form of use and purpose, but is usually 50 mass % or more, preferably 80 mass % or more, and may even be 100 mass %.

[0044] 1-3. Polymerization initiator As described above, in the specific dental material composition, it is permissible to contain some components of a polymerization initiator consisting of multiple components in a state in which the polymerization initiator does not exhibit polymerization initiation ability at temperatures below 50°C, or to contain a photopolymerization initiator and / or a thermal polymerization initiator (which does not exhibit polymerization initiation ability at temperatures below 50°C).

[0045] In the specific dental hardenable composition, the polymerization initiator is mostly a radical polymerization initiator, specifically, three types of initiators are used: a photopolymerization initiator, a thermal polymerization initiator, and a chemical polymerization initiator (room temperature redox initiator). As for the photopolymerization initiator and the thermal polymerization initiator that does not exhibit polymerization initiation ability at a temperature of 50° C. or less, those that can be used in conventional dental hardenable compositions can be used without any particular restrictions.

[0046] Examples of the photopolymerization initiator include α-diketones such as camphorquinone and benzil, ketals such as benzil dimethyl ketal and benzil diethyl ketal, thioxanthones such as 2-chlorothioxanthone and 2,4-diethylthioxanthone, and acylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0047] These photopolymerization initiators are generally used in combination with amines such as ethyl 4-dimethylaminobenzoate and N,N-di(2-hydroxyethyl)-p-toluidine, aldehydes such as dimethylaminobenzaldehyde and terephthalaldehyde, and compounds having a thiol group such as 2-mercaptobenzoxazole and decanethiol as reducing agents. Acylphosphine oxide photopolymerization initiators can also be used alone.

[0048] These photopolymerization initiators are used alone or in combination. The amount of the photopolymerization initiator is usually in the range of 0.001 to 15% by mass, preferably 0.1 to 10% by mass, based on the total amount (100 parts by mass) of the specific dental material composition.

[0049] Examples of the thermal polymerization initiator (hereinafter also referred to as "oxidizing agent") include diacyl peroxides such as benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, and m-toluoyl peroxide; peroxy esters such as t-butyl peroxybenzoate, bis-t-butylperoxyisophthalate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, t-butylperoxy-2-ethylhexanoate, and t-butylperoxyisopropyl carbonate; dialkyl peroxides such as dicumyl peroxide, di-t-butyl peroxide, and lauroyl peroxide; peroxy ketals such as 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane; ketone peroxides such as methyl ethyl ketone peroxide; and hydroperoxides such as t-butyl hydroperoxide. For example, when a thermal polymerization initiator is used in a denture base relining material consisting of one paste, the method is to apply it to the oral cavity, shape it, then remove it from the oral cavity and heat it to polymerize it. These thermal polymerization initiators are used alone or in combination. The amount of the thermal polymerization initiator is usually in the range of 0.01 to 15 parts by mass, preferably 0.1 to 10 parts by mass, based on the entire specific dental material composition (100 parts by mass).

[0050] When a chemical polymerization initiator (room temperature redox initiator) is used as a polymerization initiator, it is necessary to mix some of the components constituting the chemical polymerization initiator in a state that does not exhibit polymerization initiation ability at a temperature of 50°C or less. As the chemical polymerization initiator (composed of a combination of multiple components), any of those usable in conventional dental hardenable compositions, specifically, polymerization initiators consisting of two or more components that generate polymerization active species at around room temperature by mixing all the components immediately before use, can be used without any particular restrictions. For example, redox polymerization initiators such as organic peroxide / amine and organic peroxide / amine / sulfinic acid (or salt thereof) are preferably used. As the oxidizing agent, the same as the above-mentioned heat polymerization initiator can be used. These oxidizing agents are used alone or in combination. The amount of these oxidizing agents is usually in the range of 0.01 to 15 parts by mass, preferably 0.1 to 10 parts by mass, based on the entire specific dental material composition (100 parts by mass). The reducing agent may be, for example, a tertiary amine such as N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, 4-tert-butyl-N,N-dimethylaniline, or 2-[4-(dimethylamino)phenyl]ethan-1-ol. The reducing agent may be used alone or in combination. The amount of the reducing agent is usually in the range of 0.01 to 15 parts by mass, preferably 0.1 to 10 parts by mass, based on the total amount of the specific dental material composition (100 parts by mass).

[0051] For a dental hardening composition to be hardened in the oral cavity or a specific dental material composition which is a raw material composition thereof, it is preferable to use a photopolymerization initiator and / or a chemical polymerization initiator.

[0052] 1-4.Optional ingredients The specific dental material composition may contain optional components depending on the purpose. For example, in order to thicken the viscosity of the paste, it may contain a non-crosslinked resin that dissolves in the polymerizable monomer that constitutes the paste-like dental material. Here, the non-crosslinked resin that is soluble in the polymerizable monomer that constitutes the paste-like dental material is one in which the solubility of the non-crosslinked resin in the (a) fluorine-containing (meth)acrylate monomer is preferably 20% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass. If the solubility of the non-crosslinked resin in the (a) fluorine-containing (meth)acrylate monomer is less than 20% by mass, the paste cannot be sufficiently thickened. Examples of such optional components that can be added include polymerization inhibitors (e.g., hydroquinone, hydroquinone monomethyl ether, butylhydroxyl toluene, etc.), polymerization accelerators (e.g., borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, halogen compounds, thiourea compounds), polymerization inhibitors (e.g., butylhydroxytoluene, methoxyhydroquinone), polymerization regulators (e.g., α-methylstyrene dimer), ultraviolet absorbers (e.g., benzophenone), pH adjusters, antibacterial agents, plasticizers, pigments, dyes, fragrances, and fibers for mimicking blood vessels.

[0053] 2. Regarding the resin film constituting the bag of the packaging body of the present invention The package of the present invention comprises a bag having a storage chamber in which the dental material composition is liquid-tightly stored and which contains a polymerizable monomer and a filler, and the bag must be made of a single-layer film or multi-layer film having a layer containing a cyclic polyolefin resin in order to stably store the specific dental material composition containing a fluorine-containing (meth)acrylate for a long period of time. If a bag made of a resin film made of polypropylene or polyethylene, for example, that does not have a layer containing a cyclic polyolefin resin, is used, the content of the fluorine-containing (meth)acrylate in the specific dental material composition is likely to decrease during storage.

[0054] Here, the cyclic polyolefin resin means a polyolefin resin having a cyclic aliphatic hydrocarbon in the main chain or side chain, and includes hydrogenated ring-opening metathesis polymers (COPs) obtained by polymerizing cyclic olefins by a metathesis ring-opening polymerization reaction, and copolymers of cyclic olefins and α-olefins (chain olefins), i.e., cyclic olefin copolymers (COCs).

[0055] As the cyclic olefin, any cyclic hydrocarbon having an ethylenically unsaturated bond and a bicyclo ring can be used, but in particular, those having a bicyclo[2.2.1]hept-2-ene (norbornene) skeleton are preferred. Specifically, bicyclo[2.2.1]hept-2-ene and its derivatives, tricyclo[4.3.0.1 2,5 ]-3-decene and its derivatives, tricyclo[4.4.0.1 2,5 ]-3-undecene and its derivatives, tetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene and its derivatives, pentacyclo[6.5.1.1 3,6 .0 2,7 .0 9,13 ]-4-Pentadecene and its derivatives, pentacyclo[7.4.0.1 2,5 .1 9,12 .0 8,13 ]-3-Pentadecene and its derivatives, pentacyclo[6.5.1.1 3,6 .0 2,7 .0 9,13 ]-4,10-Pentadecadiene and its derivatives, Pentacyclo[8.4.0.1 2,5 .1 9,12 .0 8,13 Examples of the cyclic olefin include, but are not limited to, hexadecene, 3-hexadecene, and derivatives thereof. The cyclic olefin may have a polar group such as an ester group, a carboxyl group, or a carboxylic anhydride group as a substituent.

[0056] As the α-olefin to be copolymerized with the cyclic olefin, ethylene and α-olefins having 3 to 20 carbon atoms can be used. Specific examples include ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, and 4-methyl-1-pentene, and preferably ethylene.

[0057] The ring-opening metathesis polymer can be produced by ring-opening polymerization of the above-mentioned cyclic olefin using a polymerization catalyst. The cyclic olefin copolymer can be produced by random polymerization of 25 to 45 mol % of an α-olefin and 55 to 75 mol % of a cyclic olefin using a single-site catalyst such as a metallocene catalyst or a multi-site catalyst.

[0058] Compared with a copolymer (COC) of a cyclic olefin and an α-olefin (chain olefin), a ring-opening metathesis polymer (COP) has many alicyclic structures, and therefore can reduce the amount of volatilization of fluorine-containing (meth)acrylate when used as a film. For this reason, in the present invention, it is more preferable to use a ring-opening metathesis polymer (COP). As such a cyclic polyolefin resin such as COC or COP, a commercially available product can be used as it is or in a blend with other resins (polymers) (hereinafter, a resin obtained by polymer-blending a cyclic polyolefin resin with other resins is also referred to as a "blend resin"). From the viewpoint of heat fusion properties when forming the peripheral portion 4 and the weakened seal portion 5 of the bag body 2 by heat fusion, it is preferable to use it in a blend with other resins, and examples of such other resins include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene (LLDPE), ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylic acid ester copolymer, ionomer, polypropylene, etc. The other resins to be combined with the cyclic polyolefin resin may be one or more. The proportion of the cyclic polyolefin resin when blended is preferably 5 to 70% by mass, particularly 20 to 60% by mass. Furthermore, additives such as heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, antibacterial and antifungal agents, antistatic agents, lubricants, pigments, and dyes may be added within a range that does not impair the effects of the present invention.

[0059] When using a film made of only a cyclic polyolefin resin or a blend resin with a cyclic polyolefin resin content of 60% by mass, particularly more than 70% by mass, it is preferable to use a multilayer film laminated with a sealant layer made of a sealant resin film that does not contain a cyclic polyolefin resin, or a blend resin film with a cyclic polyolefin resin content of 60% by mass or less, from the viewpoint of ease of adjusting the bonding strength when forming the peripheral portion 4 and the weakened seal portion 5 of the bag body 2 by heat fusion. Suitable examples of the sealant resin include linear low density polyethylene (LLDPE), unstretched polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylic acid ester copolymer, ionomer, etc.

[0060] The resin film constituting the bag body 2 may be a single-layer film consisting of a layer of a resin containing a cyclic polyolefin resin, i.e., a resin blended with a cyclic polyolefin resin and another resin, but a base layer or intermediate layer consisting of a film made of another resin can be provided to impart gas or water vapor barrier properties. As such a multilayered film, for example, a film consisting of two layers of a base layer / sealant layer as shown in FIG. 4(A), a film consisting of a base layer / intermediate layer / sealant layer as shown in FIG. 4(B), or a film consisting of five layers of a base layer / adhesive layer / intermediate layer / adhesive layer / sealant layer as shown in FIG. 4(C) is preferable. The layer consisting of a resin containing a cyclic polyolefin resin can be used as any of the base layer, intermediate layer, and sealant layer, but the sealant layer is preferably made of the resin described above.

[0061] Resins other than the cyclic polyolefin resins used in each layer of the multilayer film may be appropriately selected depending on the purpose. For example, when a base layer is provided to enhance the strength and stiffness of the film, polyethylene terephthalate (PET), oriented polypropylene (OPP), etc. are preferably used, and when an intermediate layer is provided to improve the water vapor barrier property, ethylene-vinyl alcohol (EVOH), nylon, etc. are preferably used.

[0062] The monolayer film or multilayer film can be produced as an unstretched sheet by, for example, melting (and kneading as necessary) the raw resin (composition) in a monoaxial or twin-axial extruder, extruding it into a film shape through a T-die (die), and quenching and solidifying it with a casting roll. As a lamination method, the multilayer film can be suitably produced by sandwich laminating the films constituting each layer. In this case, the thickness of the entire monolayer film or multilayer film is preferably 40 to 200 μm, which maintains an appropriate strength when preparing a paste-like dental material in the package, and does not reduce the operability of the paste mixing operation in the package 1. In addition, in order to bond each layer of the multilayer film, an adhesive or adhesive resin that becomes the adhesive layer 14 in FIG. 4(C) can be appropriately used. Furthermore, each layer of the multilayer film can contain the above-mentioned additives as in the case of a monolayer film, within a range that does not impair the effects of the present invention, and the outer surface may be printed as necessary. However, in order to ensure visibility for checking the state of the contents, it is preferable that at least a part of the resin film constituting the bag body 2 has transparency.

[0063] 3. Packaging of the Present Invention The package of the present invention will be described below with reference to the drawings. As shown in FIG. 1, the package 1 of the present invention includes a bag body 2 having one or more storage chambers 3 partitioned by a peripheral portion 4, and a specific dental material composition liquid-tightly stored in the storage chamber (3 in FIG. 1(A) and 3a and 3b in FIG. 1(B)), i.e., a "slurry or paste-like dental material composition containing a polymerizable monomer and a filler containing a fluorine-containing (meth)acrylate" 10. When the package has a plurality of storage chambers, it is sufficient that the specific dental material composition is liquid-tightly stored in at least one storage chamber, and the other storage chambers may store a "slurry or paste-like dental material composition containing a polymerizable monomer and a filler not containing a fluorine-containing (meth)acrylate", a "liquid dental material composition containing a polymerizable monomer and not containing a filler", or a "powdered dental material composition containing a filler and not containing a polymerizable monomer".

[0064] The embodiment of the package of the present invention having only one storage chamber as shown in Fig. 1(A) is useful as a packaging form for storing a dental curable composition in a slurry or paste form, such as a photopolymerizable or thermosetting CR using a fluorine-containing (meth)acrylate as a monomer component, in a required amount in small portions for a long period of time. In this form, the surgeon (or user) cuts off at least one side of the peripheral portion 4, opens the storage chamber 3, and takes out the dental curable composition contained therein for use.

[0065] In addition, the embodiment having a plurality of the storage chambers as shown in Fig. 1(B) and Fig. 2 is useful as a packaging form for preparing a paste-like dental hardenable composition when used. For example, when using the paste-like dental material package 1 of Fig. 1(B), at least one edge 4 (e.g., 4a in Fig. 2(B)) in contact with each storage chamber (3a, 3b) is cut off, the storage chambers (3a, 3b) are opened, and each dental material composition is taken out into a dental mixing dish or kneading paper, etc., and homogenized with a mixing tool such as a spatula, whereby a paste-like dental hardenable composition is prepared when used.

[0066] In the embodiment having a plurality of the storage chambers, the packaging for preparing a dental paste-like hardenable composition of the present invention is preferable from the viewpoint of convenience of preparation at the time of use. That is, as shown in Fig. 2, the bag body 2 has at least one weakened seal part 5 and at least two storage chambers 3a, 3b partitioned by the at least one seal part 5, the weakened seal part 5 is formed so as to be rupturable by a pressing force applied to at least one of the at least two storage chambers in which the dental material composition is stored, and after the weakened seal part 5 is broken, the storage chambers 3a, 3b are communicated with each other, and all the types of dental material compositions stored in these storage chambers are mixed in the communicated storage chambers, so that a dental paste-like hardenable composition containing a polymerizable monomer containing a fluorine-containing (meth)acrylate, a filler, and a polymerization initiator can be prepared.

[0067] In this embodiment, the bag body 2 is a flat bag made of a heat-sealable film, and is partitioned to have at least one or more storage chambers 3. These storage chambers 3 are preferably rectangular, but other shapes can be used as long as they do not interfere with the mixing of the paste inside the bag body 2 of FIG. 2. It is also possible to round the corners to improve mixing efficiency. The peripheral portion 4 of the bag body 2 is sealed by heat welding at a predetermined width. In addition, for example, when a weakened seal portion 5 is formed between adjacent storage chambers as in the bag body 2 of FIG. 2, in this embodiment, the weakened seal portion 5 is formed by heat welding, but the sealing force is weaker than the heat welding of the peripheral portion 4 of the bag body 2 described above. The seal strength of the weakened seal portion 5 is such that, under normal conditions, the storage chamber 3a, which is one of the two storage chambers separated by the weakened seal portion 5, can store "agent i" consisting of "specific dental material composition" while maintaining liquid-tightness (preferably liquid-tight and air-tightness), and the other storage chamber 3b can store "agent ii" consisting of "specific dental material composition", "slurry or paste-like dental material composition containing polymerizable monomer and filler not containing fluorine-containing (meth)acrylate", "liquid dental material composition containing polymerizable monomer and not containing filler", or "powdered dental material composition containing filler and not containing polymerizable monomer" while maintaining liquid-tightness (preferably liquid-tight and air-tightness) when it contains a monomer, and without powder leakage (preferably air-tight) when it is a powder material, but when a pressing force is applied to the storage chamber 3a during use, for example, the strength is such that it breaks. On the other hand, the heat welding of the peripheral portion 4 has a strength that does not break against the pressing force.

[0068] From the viewpoint that the weakened seal portion 5 of the bag body 2 is unlikely to break due to long-term vibration or impact such as dropping during handling during transportation or storage, but can be easily broken during use, it is preferable that the seal strength of the weakened seal portion 5 is 3 to 20 (N / 15 mm), particularly 5 to 10 (N / 15 mm). Here, the seal strength means the seal strength (unit: N / 15 mm, or N / 15 mm width) measured on a test piece obtained by cutting a 15 mm wide test piece from a sample with one end heat-sealed, based on JIS Z 1707.

[0069] 4. Manufacturing method of the package of the present invention The package 1 of the present invention can be suitably produced by the following methods (1) to (7). (1) is a method for producing a bag 2 having one storage chamber and no weakened seal portion as shown in Fig. 1(A), (2) to (4) are methods for producing a bag 2 having two storage chambers and no weakened seal portion as shown in Fig. 1(B), and (5) to (7) are methods for producing a bag 2 in the package for preparing a paste-like dental curable composition of the present invention having two storage chambers and including a weakened seal portion as shown in Fig. 2.

[0070] (1) A method in which the resin film constituting the bag body 2 is heat-sealed (in the case of a multilayer film having a sealant layer, the sealant layers are heat-sealed together) to form a flat bag with one opening, specifically a three-sided (sealed) bag or a pillow bag, and then, with the opening of the flat bag facing upward, a desired amount of a specific dental material composition is supplied and contained therein, and if necessary, a predetermined amount of air is mixed in, and then the upper peripheral portion 4 is heat-sealed to seal the opening and form a containment chamber.

[0071] (2) A method in which the resin film constituting the bag body 2 is heat-sealed (in the case of a multilayer film having a sealant layer, the sealant layers are heat-sealed together) to form a flat bag with one opening, specifically a three-sided (sealed) bag or a pillow bag, and then, with the opening of the flat bag facing upward, a desired amount of "agent (i)" is supplied and contained therein, a predetermined amount of air is mixed in as necessary, and then the upper part above the part containing "agent (i)" is heat-sealed to form peripheral portion 4e and storage chamber 3a, and then a predetermined amount of "agent (ii)" is supplied and contained through the opening, and then the upper peripheral portion 4 is heat-sealed to hermetically seal the opening and form storage chamber 3b.

[0072] (3) A method in which the resin film constituting the bag body 2 is heat-sealed (in the case of a multilayer film having a sealant layer, the sealant layers are heat-sealed together) to obtain a cylindrical body with both ends open, and then a predetermined position on the body is heat-sealed perpendicular to the longitudinal direction of the cylindrical body to form a peripheral portion 4e, and then a desired amount of "agent (i)" is supplied through one opening and contained therein, and if necessary, a predetermined amount of air is mixed in and the opening is heat-sealed to seal the opening, thereby forming a storage chamber 3a, and then a predetermined amount of "agent (ii)" is supplied through the other opening and contained therein, and the opening is heat-sealed to seal the opening, thereby forming a storage chamber 3b.

[0073] (4) A method in which the resin film constituting the bag body 2 is heat-sealed (in the case of a multilayer film having a sealant layer, the sealant layers are heat-sealed together to obtain a tubular body with both ends open, and then a predetermined position of the body is heat-sealed parallel to the longitudinal direction of the tubular body to form a peripheral portion 4e and to form a tubular body in which each of the openings at both ends is divided into two and the two tubular bodies are connected by the peripheral portion 4e, and the two openings at one end are heat-sealed to form the storage chamber 3a and the storage chamber 3b, and then a predetermined amount of "agent (i)" (and a predetermined amount of air, if necessary) and a predetermined amount of "agent (ii)" (and a predetermined amount of air, if necessary) are supplied from the two openings at the other end to the storage chamber 3a and the storage chamber 3b, respectively, and then the two openings at the other end are heat-sealed.

[0074] Incidentally, even when the weakened seal portion 5 is to be formed in the bag body 2, it can be manufactured by replacing the peripheral edge portion 4e with the weakened seal portion 5 in the manufacturing methods (2) to (4).

[0075] (5) A method in which the resin film constituting the bag body 2 is heat-sealed (in the case of a multilayer film having a sealant layer, the sealant layers are heat-sealed together) to form a flat bag with one opening, specifically a three-sided (sealed) bag or a pillow bag, and then, with the opening of the flat bag facing upward, a desired amount of "agent (i)" is supplied and contained through the opening, a predetermined amount of air is mixed in as necessary, and then the upper part above the part containing the powder material is heat-sealed to form a weakened seal portion 5 and a storage chamber 3a, and then a predetermined amount of "agent (ii)" is supplied and contained through the opening, and then the upper peripheral portion 4 is heat-sealed to hermetically seal the opening and form a storage chamber 3b.

[0076] (6) A method in which the resin film constituting the bag body 2 is heat-sealed (in the case of a multilayer film having a sealant layer, the sealant layers are heat-sealed together to obtain a cylindrical body with both ends open, and then a predetermined position on the body is heat-sealed perpendicular to the longitudinal direction of the cylindrical body to form a weakened seal portion 5, and then a desired amount of "agent (i)" is supplied through one opening and contained therein, and if necessary, a predetermined amount of air is mixed in and the opening is heat-sealed and sealed to form a storage chamber 3a, and then a predetermined amount of "agent (ii)" is supplied through the other opening and contained therein, and the opening is heat-sealed and sealed to form a liquid material storage chamber 3b.

[0077] (7) A method in which the resin film constituting the bag body 2 is heat-sealed (in the case of a multilayer film having a sealant layer, the sealant layers are heat-sealed together to obtain a tubular body with both ends open, and then a predetermined position on the body is heat-sealed parallel to the longitudinal direction of the tubular body to form a weakened seal portion 5 and a tubular body in which each of the openings at both ends is divided into two and the two tubular bodies are connected by the weakened seal portion 5, and the two openings at one end are heat-sealed to form storage chamber 3a and storage chamber 3b, and then a predetermined amount of "agent (i)" (and a predetermined amount of air, if necessary) and a predetermined amount of "agent (ii)" (and a predetermined amount of air, if necessary) are supplied from the two openings at the other end to storage chamber 3a and storage chamber 3b, respectively, and then the two openings at the other end are heat-sealed.

[0078] When the package 1 has two or more storage chambers (3a, 3b, etc.), the agents to be packaged and stored in each storage chamber are appropriately selected. Also, the amount of each agent to be packaged and stored in each storage chamber is appropriately adjusted.

[0079] The amount of air contained in one or more storage chambers of the packaging body 1 is adjusted as appropriate, but it is preferable that air is contained in at least one of the one or more storage chambers of the packaging body 2 (3 in FIG. 1(A) and 3a, 3b in FIG. 1(B), etc.) and the volume of air in the storage chamber at room temperature when all the storage chambers are connected is set so that the void ratio is in the range of 15 to 40% relative to the volume of the storage chamber. If it is less than 15%, it becomes difficult to mix the two or more pastes contained in the storage chambers when two or more storage chambers are connected to each other, and if it is more than 40%, air bubbles are likely to be entrained when mixing the two or more pastes contained in the storage chambers. In the present invention, the void ratio is calculated as follows: void ratio (%)=void amount / powder-containing chamber volume×100.

[0080] 5. Method for using the package for preparing the dental paste-like hardenable composition of the present invention When the surgeon uses the packaging 1 for preparing the dental paste-like hardenable composition of the present invention shown in FIG. 2, as shown in FIG. 3(A), the surgeon takes the packaging 1 in his hand and holds it, for example, by pinching the storage chamber 3b between the thumb and index finger of both hands. Then, the paste in the storage chamber 3b is pressed into the storage chamber 3a. Then, the weakened seal portion 5 is broken in whole or in part by the pressure of the paste caused by the pressing of the storage chamber 3b and the air pressure of the air contained therein. Then, as shown in FIG. 3(B), the surgeon uses a mixing tool to press the surface (including the front, back, and both front and back sides) of the bag body 2 as necessary to mix the two agents. This pressing operation, unlike the conventional kneading and stirring, does not entrain air in the paste, and on the contrary, has the effect of pushing air bubbles contained in the paste out of the paste. Finally, as shown in Fig. 3(C), when mixing is completed, the surgeon cuts any part (e.g., 4b in Fig. 3(C)) of the peripheral portion 4 of the bag body 2 and extrudes the paste out of the bag body 2. The dental hardenable composition paste 10 taken out of the bag body 2 is formed into a desired shape and is finally polymerized in or outside the oral cavity for use. EXAMPLES

[0081] Next, test examples of this embodiment will be described, but the present invention is not limited to the following test examples. The abbreviations and titles shown in the examples are as follows.

[0082] <Raw material for dental paste> [Fluorine-containing (meth)acrylate] TFOM: 1H,1H,2H,2H-Tridecafluorooctyl methacrylate OFPM: 1H,1H,5H-Octafluoropentyl methacrylate TFPM: 2H,2H,3H,3H-Tetrafluoropropyl methacrylate [Multifunctional (meth)acrylate] HD: 1,6-Hexanediol dimethacrylate [Filling material] Cross-linked PMMA: Polymethyl methacrylate-ethylene glycol dimethacrylate copolymer (average particle size 8μm) [Organic peroxide] ·BPO: Benzoyl peroxide [Tertiary amine] ·DEPT: N,N-dihydroxyethyl-p-toluidine <Film raw material resin and material resin film> COP: Cyclic polyolefin (ZEONEX480R, manufactured by Zeon Corporation) COC: Cyclic olefin copolymer (TOPAS8007F-500, manufactured by Polyplastics Co., Ltd.) LLDPE: Linear low-density polyethylene (SP-1540, manufactured by Prime Polymer Co., Ltd.) PET: Biaxially stretched PET film with one side corona treated (T-4102, manufactured by Toyobo Co., Ltd.) PP: Non-oriented polypropylene (P-1128, manufactured by Toyobo Co., Ltd.) NY: Nylon (Unitika Ltd. emblem ONBC).

[0083] <Resin film> The above-mentioned film raw resins and material resin films were used to prepare resin films constituting the bag body 2 used in Examples 1 to 27 and Comparative Examples 1 to 3 described below. The abbreviations and layer structures of various single-layer films and laminate films are shown in Table 1.

[0084] [Table 1]

[0085] Furthermore, the films having weakened seal portions of Examples 12 to 27 were subjected to the following sealability evaluation. The results are shown in Table 2. In addition, the displays in the columns of "Sealant Layer", "Intermediate Layer", and "Base Material Layer" in Table 1 represent the resin composition (parts by mass) and thickness (μm) that constitute these for the single-layer film and each layer. For example, "COP = 100" represents a layer composed only of COP (100% by mass), and a layer where "COP / LLDPE" is "70 / 30" means a layer composed of a blend resin having a composition of 70% by mass of COP and 30% by mass of LLDPE.

[0086] (Sealing Property Evaluation Method) In the production process of the paste dental material package described later, since the weakened seal part was heat-sealed at a seal temperature of 190°C so that the seal strength was in the range of 7 to 8 N / 15 mm, when the sealant layers (S) of each film were opposed to each other and heat-sealed at a seal temperature of 190°C, the heat-sealing time required until the seal strength was in the range of 7 to 8 N / 15 mm: the required time t (seconds) was measured, and the results were evaluated based on the following evaluation criteria.

[0087] Evaluation ◎ (t ≤ 1 second): Since it easily fuses in a short time, the productivity is high. Evaluation ○ (1 second < t ≤ 2 seconds): It easily fuses, but the productivity slightly decreases. Evaluation △ (2 seconds < t ≤ 4 seconds): It is an acceptable seal time, but the productivity decreases. Evaluation × (4 seconds < t): The seal time is long, and the productivity greatly decreases.

[0088] In addition, for the required time t, three test pieces with a width of 15 mm were cut out from the samples heat-sealed by changing the heat-sealing time in accordance with JIS Z1707. Under the environment of a pulling speed of 300 mm / min and 23°C, they were pulled in a direction of 180° with respect to the heat-sealing surface between the films, the films between the test pieces were peeled off, and the maximum value of the peel strength was measured. Then, the average value of the maximum values of the peel strength of the above three test pieces was used as the seal strength, plotted on a graph with the horizontal axis being the heat-sealing time and the vertical axis being the seal strength, and the time when the seal strength reached 7.5 N / 15 mm was taken as the required time t.

[0089] [Table 2]

[0090] Example 1 (1 paste package) A paste (1) containing 2.7 parts by mass of TFOM, 2.0 parts by mass of cross-linked PEMA, and 0.1 parts by mass of BPO was prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (70 mm x 70 mm) shown in Table 1 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Next, the paste (1) was filled into the storage chamber. Finally, a predetermined amount of air was mixed into the storage chamber, and the peripheral part 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in Figure 1 (A). The volatilization of the obtained paste-like dental material package was evaluated by the method shown below. However, no volatilization (weight loss) was observed (0 mg). The results are shown in Table 3.

[0091] (Method of evaluating weight loss) The weight (mg) of the prepared paste-like dental material package was measured, and then it was stored in a thermostatic chamber at 60°C for 3 days, after which it was removed from the chamber and its weight (mg) was measured. The difference between the two weights (mg) gave the amount of weight loss (volatilization amount of fluorine-containing (meth)acrylate).

[0092] Examples 2 and 5 to 9 (one paste package) A paste (2) containing 2.7 parts by mass of OFPM, 2.0 parts by mass of cross-linked PEMA, and 0.1 parts by mass of BPO was prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (70 mm x 70 mm) shown in Table 1 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Then, the paste (2) was filled into the container. Finally, a predetermined amount of air was mixed into the container, and the peripheral part 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in Figure 1 (A). The weight loss of the obtained paste-like dental material package is shown in Table 3.

[0093] Example 3 (1 paste package) A paste (3) containing 2.7 parts by mass of TFPM, 2.0 parts by mass of cross-linked PEMA, and 0.1 parts by mass of BPO was prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (70 mm x 70 mm) shown in Table 1 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Then, the paste (3) was filled into the container. Finally, a predetermined amount of air was mixed into the container, and the peripheral part 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in FIG. 1(A). The weight loss of the obtained paste-like dental material package is shown in Table 3.

[0094] Example 4 (1 paste package) A paste (4) containing 1.7 parts by mass of OFPM, 1.0 parts by mass of HD, 2.0 parts by mass of cross-linked PEMA, and 0.1 parts by mass of BPO was prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (70 mm x 70 mm) shown in Table 1 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Then, the paste (4) was filled into the container. Finally, a predetermined amount of air was mixed into the container, and the peripheral part 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in FIG. 1(A). The weight loss of the obtained paste-like dental material package is shown in Table 3.

[0095] Examples 10 and 11 (2 paste packages) A paste (5) containing 2.7 parts by mass of OFPM, 2.0 parts by mass of crosslinked PEMA, and 0.2 parts by mass of BPO, and a paste (6) containing 2.7 parts by mass of OFPM, 2.0 parts by mass of crosslinked PEMA, and 0.2 parts by mass of DEPT were prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (100 mm x 70 mm) shown in Table 2 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Next, the peripheral part 4e was formed by heat-sealing at 220°C for 2 seconds so that the size of the storage chamber (i) and the storage chamber (ii) were in a 1:1 ratio. Thereafter, the above paste (5) was filled in the storage chamber (i) and the above paste (6) was filled in the storage chamber (ii). Finally, a predetermined amount of air was mixed into the storage chambers (i) and (ii), and then the peripheral part 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in FIG. 1(B). The weight loss of the resulting packaged paste-like dental material is shown in Table 3.

[0096] Examples 12 to 26 (2-Paste Package) A paste (5) containing 2.7 parts by mass of OFPM, 2.0 parts by mass of cross-linked PEMA, and 0.2 parts by mass of BPO, and a paste (6) containing 2.7 parts by mass of OFPM, 2.0 parts by mass of cross-linked PEMA, and 0.2 parts by mass of DEPT were prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (100 mm x 70 mm) shown in Table 2 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Next, the weakened seal part 5 was formed by heat-sealing at 190°C for the required time (seconds) shown in Table 2 so that the size of the storage chamber (i) and the storage chamber (ii) were in a 1:1 ratio. Then, the storage chamber (i) was filled with the paste (5), and the storage chamber (ii) was filled with the paste (6). Finally, a predetermined amount of air was mixed into the storage chambers (i) and (ii), and the peripheral portion 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in Fig. 2. The weight loss of the obtained paste-like dental material package is shown in Table 3.

[0097] Example 27 (2 paste packaging) A paste (7) containing 1.7 parts by mass of OFPM, 1.0 parts by mass of HD, 2.0 parts by mass of cross-linked PEMA, and 0.2 parts by mass of BPO, and a paste (8) containing 1.7 parts by mass of OFPM, 1.0 parts by mass of HD, 2.0 parts by mass of cross-linked PEMA, and 0.2 parts by mass of DEPT were prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (100 mm x 70 mm) shown in Table 2 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Next, the weakened seal part 5 was formed by heat-sealing at 190°C for the required time (seconds) shown in Table 2 so that the size of the storage chamber (i) and the storage chamber (ii) were in a 1:1 ratio. Then, the storage chamber (i) was filled with the paste (7), and the storage chamber (ii) was filled with the paste (8). Finally, a predetermined amount of air was mixed into the storage chambers (i) and (ii), and the peripheral portion 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in Fig. 2. The weight loss of the obtained paste-like dental material package is shown in Table 3.

[0098] Comparative Examples 1 to 3 (1 paste package) A paste (2) containing 2.7 parts by mass of OFPM, 2.0 parts by mass of cross-linked PEMA, and 0.1 parts by mass of BPO was prepared. Next, the peripheral parts 4b, 4c, and 4d of two rectangular films (70 mm x 70 mm) shown in Table 1 were heat-sealed at 220°C for 2 seconds using a 5 mm-wide heat sealer. Then, the paste (2) was filled into the container. Finally, a predetermined amount of air was mixed into the container, and the peripheral part 4a was heat-sealed at 220°C for 2 seconds to obtain a paste-like dental material package as shown in Figure 1 (A). The weight loss of the obtained paste-like dental material package is shown in Table 4.

[0099] [Table 3]

[0100] [Table 4] [Explanation of symbols]

[0101] 1. Paste-type dental material package 2 Bags 3. Containment Room 4 Periphery 5 Weakened seal 10 Slurry or paste-like dental material composition 11 Base material layer 12 Sealant layer 13. Middle Class 14 Adhesive layer

Claims

1. A dental material composition package comprising a bag having a storage chamber and a slurry or paste-like dental material composition containing a polymerizable monomer and a filler, the dental material composition being liquid-tightly stored in the storage chamber, The polymerizable monomer contains a fluorine-containing (meth)acrylate, The bag body is composed of a single-layer film or a multi-layer film having a layer containing a cyclic polyolefin resin. A dental material composition package comprising:

2. The dental material composition package according to claim 1, wherein the layer containing the cyclic polyolefin resin is made of a resin composition having a cyclic polyolefin resin content of 5 to 70% by mass and a remainder of a polyolefin resin having no ring structure.

3. 2. The dental material composition package according to claim 1, wherein the single-layer film or multi-layer film having a layer containing a cyclic polyolefin resin is a heat-sealable film.

4. The bag body has at least one weakened seal portion and at least two of the storage chambers separated by the at least one seal portion, the slurry or paste-like dental material composition containing a fluorine-containing (meth)acrylate as a polymerizable monomer is contained in at least one of the at least two containing chambers; At least one of the at least two storage chambers may contain a slurry or paste dental material composition containing a polymerizable monomer not containing a fluorinated (meth)acrylate and a filler, a liquid dental material composition containing a polymerizable monomer and not containing a filler, or a powder dental material composition containing a filler and not containing a polymerizable monomer, At least one of the dental material compositions contained in each of the containers contains a polymerization initiator, the weakened seal portion is formed so as to be breakable by a pressing force applied to at least one of the at least two chambers in which the dental material composition is contained; After the weakened seal portion is broken, the respective storage chambers are communicated with each other, and all the types of dental material compositions stored in these storage chambers are mixed in the communicated storage chambers, thereby making it possible to prepare a paste-like dental hardenable composition containing a polymerizable monomer containing a fluorine-containing (meth)acrylate, a filler, and a polymerization initiator. The dental material composition package according to claim 3.

5. The polymerization initiator includes a chemical polymerization initiator composed of two or more components each of which does not exhibit polymerization activity alone, Each of the dental material compositions contained in each storage chamber contains at least one of the two or more components constituting the chemical polymerization initiator, but does not contain all of the two or more components, Each of the two or more components constituting the chemical polymerization initiator is contained in any one of the dental material compositions contained in each of the containers. The dental material composition package according to claim 4.

6. A dental material composition package as described in claim 4, wherein air is also contained in at least one of the storage chambers, and the volume of air in the connected storage chambers at room temperature when mixing the paste-like dental material is in the range of 15 to 40% of the volume of the storage chamber.

Citation Information

Patent Citations

  • Lining material for dental plate

    JP2000312689A

  • Pharmaceutical storage bag including dental powder / liquid material and method of dispensing

    JP2014223237A

  • Dental composition

    JP2021080196A